Judgment bias, fear, and stress responses of Red Junglefowl and Athens Canadian Random Bred chickens - Victor J. Oyeniran; Rosemary H. Whittle; Sara K. Orlowski; Shawna L. Weimer (Frontiers in Animal Science)
Understanding how poultry perceive and interpret their environment is essential to enhancing their welfare. Animal welfare science relies on measures of the behavioral and physiological components of affective states (positive and negative) as welfare indicators. There has been growing interest in using the judgment bias test (JBT) to study birds’ affective states by assessing their responses to ambiguous cues. The objective of this study was to investigate the affective state of two chicken breeds with different evolutionary histories: the Red Junglefowl (RJF), the primary ancestor of modern chickens, and the Athens Canadian Random Bred (ACRB), a rustic domesticated breed, using the JBT at two ages. Another objective was to explore the effect of the JBT on the fear and stress responses of the chickens that participated in the JBT compared to those that did not (NJBT) on days (D) 35 and 63. Fear was evaluated using the tonic immobility test, and stress was measured noninvasively from thermal images of the eye and beak. Chickens successfully discriminated between positive (POS) and neutral (NEU) JBT cues, showing shorter latencies to approach the POS cue (P < 0.0001). While there were no breed differences on D29 of the JBT, RJF chickens exhibited shorter latencies to approach cues than ACRB on D60 (P < 0.001). Independent of testing at both ages, RJF had a longer duration of tonic immobility than ACRB (P < 0.01), indicating higher fearfulness. While the JBT did not affect D35 tonic immobility, JBT chickens had longer tonic immobility durations than NJBT on D63 (P < 0.05). Chickens that participated in the JBT had lower eye and beak minimum surface temperatures than NJBT (P < 0.05), indicating that the JBT may have increased stress post-testing. These findings highlight the influence of domestication on the affective states and the importance of considering fear and stress in measuring the affective states of chickens.